Characteristics of Amino Acid Profiles of Catfish (Pangasius sp.)Meat Based on Habitat - Damanik, Apriliani Maranatha; Ilza, Mirna; Edison, Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Theaim of the study was to determinethe different characteristics of essential and non-essential amino acids and value of chemical composition on catfish meat originating from natural rivers and from floating nets. The method used was comparative experimentalfor different habitat treatment with T-test established of 2 treatments, namely (P1 = natural river catfish, P2 = floating net catfish) with 5 replications of chemical composition and 2 replications of amino acid analysis. The experimental unit was 10 units. The parameters used were chemical analysis(moisture, ash,protein,fat,carbohydrate content) andamino acid analysis. The result showed thatthe total length of natural river catfish was 48cm and floating net catfish was 45 cm with an average weight was 1230gr.The yield of natural river catfish meat was 52.8450 g and 50.4065 g. The chemical characteristics of natural river catfish meat showed thatmoisture,ash, protein, fat, and carbohydrate was 67.2323%, 2.8648%, 21.2638%,7.2086% and1.4304%.The chemical characteristics of floating net catfish showed thatmoisture,ash, protein, fat, and carbohydrate was66.7238%,2.4701%, 20.9011%, 7.8405% and2.0642%. Leusin was the highest essential amino acids in catfish meat. Where in natural river catfish was 4.7145% and floating net catfish was 4.128%, while glutamic acid was highest non-essential amino acids in catfish meat, where in natural river catfish was 7.8695% (WW) and in floating net catfish was 6.1975% (WW). The total number of amino acids in natural river catfish was 46.043% (WW) and floating net catfish was 33.4714% (bb).   Key words: Amino acid, Catfish, and Habitat